Practices to develop self-conscience. (2011)
Starting from the premise of the evolutive psychology, which establishes human conscience development, the author suggests a series of practices to promote self-conscience growth. According to him, these practices are essential to understand and put into practice some of the suggestions of modern administrative theory, such as the ones stated in the Harvard Negotiation Method based on the differentiation between person and problem and on the unconditional respect for the being of the other, in order to develop the so called emotional intelligence. To the author, the necessary compassion to project management work to the increasing of human condition is only possible if managers have reached evolutive level, which enables them to feel other people as a part of themselves. The central point of this paper is the impossibility of obtaining enterprise human development without an evolution of manager's conscience level. The suggested practices aim to favor organizational leader development.